Environmental Efficiency of Apple Production in China: A Translog Stochastic Frontier Analysis. (August 2019) - Bai, Xiuguang; Salim, Ruhul; Bloch, Harry
Abstract : This article estimates technical and environmental efficiencies using the stochastic frontier analysis with panel data of twenty-two main apple production provinces in China during 1992–2014. Results show that the environmental efficiency for pesticide input alone has lower mean value of 0.337 than environmental efficiency for the two environmentally detrimental inputs, pesticide and chemical fertilizer, which is 0.782. Furthermore, all efficiency scores have decreasing trends over time. Loess Plateau is more environmentally efficient than the Bohai bay region. Results of output elasticities show that chemical fertilizer has a mean value of 0.225, which is higher than for material, labor, and pesticide input. Also, apple production in China experiences decreasing returns to scale. Finally, it is also discovered that labor and chemical fertilizer have a substitute relationship, while material and labor have a complementary relationship, as do chemical fertilizer and pesticide. The results from the study should prove useful for reallocating input resources and improving environmental efficiency.